Pengaruh Keamanan, Kemudahan, dan Kepercayaan Terhadap Kepuasan Pelanggan Pada PT Lion Parcel - Robin Robin; Winda Evyanto (eCo-Buss, 2023)
The purpose of this study was to determine the effect of security, convenience, and trust on customer satisfaction at PT Lion Parcel. This study was conducted using quantitative techniques. The sample of this study was used as many as 100 respondents in PT Lion Parcel customers using the Cochran formula. Questionnaires were used as a data collection technique. By using SPSS 25 software, data analysis techniques include descriptive statistics test, data quality test, classic assumption test, influence test, and hypothesis test. Based on the results of multiple linear regression, security (X1) has an effect of 0,104 or 10,4% on customer satisfaction (Y) at PT Lion Parcel, ease (X2) has an effect of 0,536 or 53,6% on customer satisfaction (Y) at PT Lion Parcel and trust (X3) has an effect of 0,245 or 24,5% on customer satisfaction (Y) at PT Lion Parcel. Safety, convenience, and trust factors affect customer satisfaction (Y) at PT Lion Parcel by 64,9% in accordance with the coefficient of determination (R2) data. Based on the hypothesis test results found that security, convenience, and confidence have a positive and significant effect partially or simultaneously on customer satisfaction at PT Lion Parcel